Effects of Methylprednisolone and Hydrocortisone on Aggregation of Rabbit Platelets Induced by Arachidonic Acid and Other Aggregating Substances - Glass, Frank; Lippton, Howard; Kadowitz, Philip J (Thrombosis and Haemostasis, 1981)
The effects of methylprednisolone and hydrocortisone on platelet aggregation induced by arachidonic acid (AA), collagen, adenosine diphosphate (ADP), prostaglandin (PG) H2, and a stable PGH2 analog, were studied in platelet-rich plasma (PRP) from the rabbit. Incubation of either steroid in PRP inhibited AA-, collagen- and ADP-induced platelet aggregation in a concentration-related manner. The dose of methylprednisolone required to inhibit 0.02 mM AA-induced aggregation was lower than that required to inhibit either 0.08 μg/ml collagen or 0.2 μM ADP-induced aggregation. Methylprednisolone produced a dose dependent inhibition of platelet aggregation induced by PGH2 and the stable PGH2 analog. In washed platelets methylprednisolone was more effective in inhibiting AA-induced aggregation than ADP- or collagen-induced aggregation; however, the difference in effect was less than in PRP. Platelet responses to AA in PRP from rabbits treated with hydrocortisone or methylprednisolone, 100 mg/kg i.v., were inhibited in a transient manner, whereas aggregation induced by ADP under similar conditions was unchanged. Since inhibition of aggregation elicited by AA occurred at concentrations which do not influence PGH2-, PGH2 analog-, collagen- or ADP-induced aggregation, the present data suggest that the steroids may inhibit the incorporation, the release, or the metabolism of arachidonic acid in platelets. The actual mechanism of this relatively specific inhibition of AA-induced aggregation by anti-inflammatory steroids is uncertain but may be related to the membrane “stabilizing” properties of methylprednisolone and hydrocortisone.
Keywords: Platelet aggregation; Anti-inflammatory glucocorticoids; Arachidonic acid; Endoperoxide prostaglandin H2; Endoperoxide analog